2004
DOI: 10.1016/j.jcrs.2004.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral cataract surgery

Abstract: This study provides evidence that SBCS by experienced surgeons is likely to be a safe and efficient procedure and is positively received by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 28 publications
4
59
2
Order By: Relevance
“…Several previous studies found that the majority of children with bilateral cataracts had a final BCDVA of 20/60 or better after primary IOL implantation, which is similar to our results. [13][14][15][16][17][18] However, Magli et al 15 determined that there were no significant differences of visual outcome between eyes that underwent primary IOL implantation and those that underwent secondary IOL implantation after simultaneous extraction of bilateral congenital cataracts, which differs from the results of our study. Furthermore, Kim et al 19 demonstrated that secondary IOL at 2 years of age showed better visual outcomes for bilateral congenital cataracts than primary implantation, given postoperative complications, such as secondary glaucoma and strabismus, and required additional surgeries.…”
Section: Discussioncontrasting
confidence: 99%
“…Several previous studies found that the majority of children with bilateral cataracts had a final BCDVA of 20/60 or better after primary IOL implantation, which is similar to our results. [13][14][15][16][17][18] However, Magli et al 15 determined that there were no significant differences of visual outcome between eyes that underwent primary IOL implantation and those that underwent secondary IOL implantation after simultaneous extraction of bilateral congenital cataracts, which differs from the results of our study. Furthermore, Kim et al 19 demonstrated that secondary IOL at 2 years of age showed better visual outcomes for bilateral congenital cataracts than primary implantation, given postoperative complications, such as secondary glaucoma and strabismus, and required additional surgeries.…”
Section: Discussioncontrasting
confidence: 99%
“…ISBCE is has a growing popularity worldwide, with some regions adopting general implementation, such as Canary Islands where 80% of all cataract surgeries are performed in this way [11]. Patient satisfaction has been reported as high, with 91% willing to recommend it to their friends and family [12]. Nevertheless, until now ISBCE has remained an exception.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these concerns, ISCS has been reported to be safe in various studies. 1,[13][14][15][16][17] In fact, even the mortality risk from a road accident while travelling to the greater number of visits required for separate surgeries or follow-up visits was calculated to be higher than the risk of bilateral endophthalmitis in simultaneous cataract surgery. 30 Similarly, ISCS was not associated with more intraoperative and post-operative complications, Bilateral cataract surgery N Nassiri et al although a larger cohort of patients and a longer followup period might be needed for a conclusive answer.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, it is still unknown whether it is better for these patients to have ISCS or delayed sequential cataract surgery (DSCS). Despite the obvious benefits of ISCS to patients and society, [8][9][10][11] the major reluctance of ophthalmologists to perform ISCS revolves to some extent around its non-catastrophic complications, such as refractive surprises, and most importantly, its catastrophic complications, such as endophthalmitis, 11 especially due to contaminated instrument-derived incidents; 12 however, the literature indicates that the safety of ISCS has been increasing, 1,[13][14][15][16][17] particularly with recent advancements of microsurgical techniques 18,19 and the use of strict protocols for post-operative endophthalmitis prophylaxis. 20 Furthermore, if an intraoperative complication occurs during the first-eye surgery, surgery for the second eye can be aborted.…”
Section: Introductionmentioning
confidence: 99%